Optics for the IASA cw RTM - Sparveris, N.; Filippas, A. V.; Herminghaus, H.; Hizanidis, K.; Karabarbounis, A.; Papadakis, N.; Papanicolas, C. N.; Stiliaris, E.; Vodinas, N. (HNPS Advances in Nuclear Physics, 2019)
A Continuous Wave Cascade Racetrack Microtron (RTM) is being built at the Institute of Accelerating Systems and Applications (IASA). Making optimal use of the available equipment (obtained from NIST and the University of Illinois), a two-stage ν = 1 Cascade scheme with optics similar to those of the Mainz RTM was adopted. The IASA CW RTM will provide a variable output energy from 6.5 to 246 MeV, with current intensity exceeding ΙΟΟμΑ The LANL side-coupled linear accelerator structure operates at the RF frequency of 2380 MHz. The new design provides excellent emittance characteristics. Details of the optics design and results of the 100 keV beam Line of the Athens CW Cascade RTM are presented.